The Educational Significance of Folk Games in Palestine: A Descriptive Analytical Field Study Sanabel Center for Studies and Folk Heritage - Sa'ir - sakar djaradat Mohamed, idris (sports creativity, 2025)
The study concerned to clarify the educational indication of the folkloric popular customs popular grape in Palestine to achieve the following goals : 1- reviving of this important side from our folklore . 2- working to reduce a huge suffering which the child exposes to these pains in daily exercises. 3- offering information to serve the decision makers in taking positive steps in drawing the general policy and execution the future plans to achieve of adaptation of the child character and also to response his/ her needs within the reality that liver in The study tried to answer the following questions : 1- what are the dominant popular playing that are exercised in the popular reality? 2- what is the educational indication of each popular playing? 3- what are the educational strategies derived from the popular playing? The study followed the field descriptive approach for observing the popular playing- popular games- and its exercise in the regions of Hebron and Bethlehem and specific sides to observing the popular plying in terms of the games race their goal and their exercise place the games persons, the games subject and their costs and their execution measures and the surrounding environmental circumstances . Also the recorder depended the analytic approach for the educational indication for each popular games which using the intended note of the playing games which exercised with returning to the bulletins books periodicals and folklore centers archive. each popular games is analyses with showing its benefit and its educational value and the study attained- reached- to a group of the educational strategies its more important the psychological, educational and cognitive and also the strategies of belonging friendship, benefit and opposite. The study pointed to a group of suggestions research and general recommendations and the academic for the completion of scientific studies holding in this field